Muhammad Haji Salleh and the Malay Annals - Aveling, Harry (Asiatic: IIUM Journal of English Language and Literature, 2020)
The Malay Annals (Sejarah Melayu or Sulalatus Sulatin) is the most respected of Malay classical literary texts. In 1981, Muhammad Haji Salleh published a volume of poems based on the chapters of the Sejarah Melayu, called Sajak-Sajak Sejarah Melayu. He has translated twelve of these poems into English and they appear regularly in English language collections of his poetry. This article analyses the major themes underlying Muhammad’s whole text: the role of the poet as a moral and philosophical guide; the principles of characterisation employed; and the moral principles that sustain personal virtue and the state.